2022
DOI: 10.3389/fneur.2022.820858
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding RNA Regulatory Network in Ischemic Stroke

Abstract: Stroke is a worldwide public health problem that has caused a substantial economic burden to families and society. Despite recent major advances, there is still a need for more timely, effective diagnosis and treatment methods for acute ischemic stroke. Non-coding RNAs (ncRNAs), which widely exist in the human body, do not encode proteins. Instead, these mediate various cellular processes as functional regulatory molecules from the RNA level. Each ncRNA node in organisms is not isolated but constitutes a compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 95 publications
(88 reference statements)
0
0
0
Order By: Relevance
“…Our study also focused on non-coding RNAs associated with these critical genes. Previous studies have shown that non-coding RNAs play an essential regulatory role in IS through various pathways, such as apoptosis, oxidative stress, activation of microglia, and regeneration of vascular endothelial cells [43]. As an important regulatory factor of IS, miRNA is involved in the occurrence and regulation of ischemic nerve tissue inflammation and has potential application value for the neuroprotection and neovascularization of IS [24].…”
Section: Discussionmentioning
confidence: 99%
“…Our study also focused on non-coding RNAs associated with these critical genes. Previous studies have shown that non-coding RNAs play an essential regulatory role in IS through various pathways, such as apoptosis, oxidative stress, activation of microglia, and regeneration of vascular endothelial cells [43]. As an important regulatory factor of IS, miRNA is involved in the occurrence and regulation of ischemic nerve tissue inflammation and has potential application value for the neuroprotection and neovascularization of IS [24].…”
Section: Discussionmentioning
confidence: 99%